2012
DOI: 10.1016/j.envres.2012.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Mercury in tropical and subtropical coastal environments

Abstract: Anthropogenic activities influence the biogeochemical cycles of mercury, both qualitatively and quantitatively, on a global scale from sources to sinks. Anthropogenic processes that alter the temporal and spatial patterns of sources and cycling processes are changing the impacts of mercury contamination on aquatic biota and humans. Human exposure to mercury is dominated by the consumption of fish and products from aquaculture operations. The risk to society and to ecosystems from mercury contamination is growi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 144 publications
0
32
0
2
Order By: Relevance
“…20,37 The GEOS-Chem model predicted moderately high and fairly uniform Hg deposition (range 8−14 μg m −2 yr −-1 ) in tropical oceans worldwide. 22 GEOS-CHEM predicted wet Hg deposition of >18 μg m −2 yr −1 in the area just north of PR (20°N, southern limit of results presented), and indicated that less than 10% of Hg deposition to this area originates from North American primary anthropogenic sources. 12 …”
Section: ■ Discussionmentioning
confidence: 89%
“…20,37 The GEOS-Chem model predicted moderately high and fairly uniform Hg deposition (range 8−14 μg m −2 yr −-1 ) in tropical oceans worldwide. 22 GEOS-CHEM predicted wet Hg deposition of >18 μg m −2 yr −1 in the area just north of PR (20°N, southern limit of results presented), and indicated that less than 10% of Hg deposition to this area originates from North American primary anthropogenic sources. 12 …”
Section: ■ Discussionmentioning
confidence: 89%
“…As apex predators, many marine mammal species are exposed to high concentrations of anthropogenic contaminants, which increase their likelihood of experiencing negative health effects (Bossart 2011; Costa et al 2012; Dietz et al 1998). Trace element toxicity is known to cause a myriad of sub-lethal and lethal effects in marine mammals such as suppression of the immune system, neurotoxicity, and general reduced fitness (De Guise et al 1995; Kakuschke and Prange 2007; Lavery et al 2009; Lynes et al 2006; Lynes et al 2007; Pellisso et al 2008; Siebert et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The timing offset between decreases in GEM and fetch-component radon in the early wet and late dry seasons suggests that air mass origin is not the only influence on wet-season GEM decreases. Within tropical regions, wet deposition has been shown to be a significant pathway for mercury from the atmosphere to both oceanic and terrestrial ecosystems, even in relatively low-mercury air and despite the low solubility of mercury in its elemental form (Fostier et al, 2000;Costa et al, 2012;Hansen and Gay, 2013;Soerensen et al, 2014;Shanley et al, 2015). Mercury "rainout" -or the tendency for mercury rainwater loading to decrease with increasing precipitation -has also been demonstrated in Mercury Deposition Network (MDN) data in North America (Glass and Sorensen, 1999;Prestbo and Gay, 2009) and positive correlations between GEM (TGM) and rainwater mercury have been reported in MDN data (GEM; Cole et al, 2014) and at Cape Point, South Africa (TGM; Brunke et al, 2016).…”
Section: Overall Means and Seasonal Trendsmentioning
confidence: 99%
“…The tropics also represent an important region for mercury cycling as they are home to around 40 % of the world's population, including over 50 % of people under the age of 15, a group at greater risk of adverse effects due to mercury exposure during early development (Bose-O'Reilly et al, 2010). Furthermore, this region hosts several large coastal communities within emerging and developing economies, in which environmental controls and advisories are not always well developed (Costa et al, 2012).…”
mentioning
confidence: 99%